2014
DOI: 10.2147/cwcmr.s67054
|View full text |Cite
|
Sign up to set email alerts
|

Objective evaluation for venous leg ulcer-related nociceptive pain using thermography

Abstract: Correspondence: hiromi sanada 7-3-1 hongo, Bunkyo-ku, Tokyo 113-0033, Japan Tel +81 3 5841 3419 Fax +81 3 5841 3419 email hsanada-tky@umin.ac.jp Purpose: We aimed to identify distinguishing characteristics in thermographic images of venous leg ulcer (VLU), for objective evaluation of VLU-related nociceptive pain. Patients and methods: Secondary analysis was performed, using existing data obtained from April to November 2010, for patients with VLU. Thermographic images of wounds and their surrounding area were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…periwound skin > wound edge > wound bed). This pattern is observed in almost all cases that heal normally . In some cases that differ from the pattern mentioned above, the temperature is lower at the wound edge than at the periwound skin and wound bed (periwound skin and wound bed > wound edge) (Figure ).…”
Section: Methodsmentioning
confidence: 63%
See 3 more Smart Citations
“…periwound skin > wound edge > wound bed). This pattern is observed in almost all cases that heal normally . In some cases that differ from the pattern mentioned above, the temperature is lower at the wound edge than at the periwound skin and wound bed (periwound skin and wound bed > wound edge) (Figure ).…”
Section: Methodsmentioning
confidence: 63%
“…Our previous study using thermography focused on the mechanism underlying the relative temperature increase caused by increased blood flow via significant vasodilation due to the inflammatory response . On the other hand, this study is a new investigation focusing on a relative temperature decrease based on deficient blood flow in the devitalised tissue at the wound edge.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously reported that a high temperature specifically at the periwound area on thermography may well be an indicator of a painful wound [14]. However, thermography cannot be used to assess neuropathic pain that is not accompanied by a temperature elevation.…”
Section: Introductionmentioning
confidence: 99%